Serum folate and homocysteine as biomarkers for suicide risk in major depressive disorder: insights in males and younger patients - Anqi Zhang; Yuncong Qin; Han Wang; Nan Lyu; Qian Zhao; Ling Zhang; Juan Huang (BMC Psychiatry)
Abstract Background Major depressive disorder (MDD) is a leading contributor to the global disease burden, with suicide constituting a critical complication. Current clinical assessment tools are limited by subjectivity and diagnostic delays, highlighting the urgent need for objective biomarkers to enable early detection of suicide risk. Methods We conducted a retrospective observational study by extracting electronic health records (EHRs) from the Hospital Information System of Beijing Anding Hospital. A total of 1,115 patients diagnosed with MDD between January 1, 2013, and December 31, 2020, were identified. Using propensity score matching (PSM), 483 patients exhibiting suicidal ideation or behavior (MDS) were matched to 483 non-suicidal controls (MDNS). Binary logistic regression analyses were performed to assess the associations between suicide risk and serum levels of folate, homocysteine (HCY), C-reactive protein (CRP), adrenocorticotropic hormone (ACTH), and testosterone. Results After PSM, higher serum folate levels (> 6 ng/mL) were significantly associated with a reduced risk of suicidal ideation or behavior (OR = 0.648; 95% CI: 0.496–0.847; p = 0.001). This association was particularly pronounced among male patients (OR = 0.569; 95% CI: 0.338–0.959; p = 0.034) and individuals aged ≤ 45 years (OR = 0.561; 95% CI: 0.394–0.799; p = 0.001). Furthermore, lower HCY levels (≤ 11.1 µmol/L) were positively associated with suicide risk among individuals aged ≤ 45 years (OR = 0.617; 95% CI: 0.409–0.931; p = 0.022). No significant associations were found between CRP, ACTH, or testosterone levels and suicide risk. Conclusion Serum folate and HCY levels may serve as potential biomarkers for assessing suicide risk in patients with MDD, particularly in specific demographic subgroups. Further longitudinal studies are needed to validate these findings and explore the underlying mechanisms.